Evaluating students pattern of interaction in online courses - Junaidi, Juhazren (2014)
The primary focus in the research of online learning is interaction, which is central to an educational experience (Garrison & Cleveland-Innes, 2005). Although interaction alone does not represent participation (Garrison, Anderson & Archer, 2000), however interaction could promote participation and engage students in learning (Hrastinski, 2009). Researchers have widely agreed that in an e-learning environment, students could learn better by participating (Hrastinski, 2009). As distinguished by Moore (1989) that there are three dimensions of interaction in an e-learning environment: learner-instructor, learner-content and learner-learner. It has been suggested that participation of a student can be measured by accumulating the interactions that occurred in an e-learning forum (Davies & Graff, 2005; Lipponen et al., 2003). One of the key challenges in e-learning is to encourage participation (Bento & Schuster, 2003), which means that students need to be encouraged to interact online. By participating, students will find themselves taking part in the learning process. Vonderwell and Zachariah (2005) noted that through interactions, students will become interdependent, able to share learning goals and information, creating path towards effective learning. Previous research had indicated that participation when measured as interaction with peers and instructors, stimulated and encouraged perceived learning (Hrastinski, 2008).